REVOLUTIONARY EUROPE AND THE DESTRUCTION OF JAVA’S OLD ORDER, 1808-1830 - Carey, Peter (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
At first glance, it may seem strange that Java, an island situated half a world away from France Revolutionary, should the end up being one of the key battle grounds in the global conflict which followed with the fateful Girondin decision to declare war on Austria in the spring of 1792. Yet, in the compass of less than a decade, Java’s own ancient regime that was violently overturned as in quick succession of a Franco-Dutch regime (1808-11) under Napoleon’s only non-French marshal, Herman Willem Daendels (1762-1818), and a five-year British occupation (1811-1816) under the equally dictatorial Sir Thomas Stamford Raffles (1781-1826), transformed the colony. This paved the way for the restoration of Dutch rule in 1816 under the terms of the Treaty of Vienna by which time the commercial dealings of the Company had been replaced by the beginnings of a modern colonial state, the post-January 1818 Netherlands Indies. Over the next century, this would reduce the power of the local rulers and establish Dutch authority in nearly every corner of the archipelago. The boundaries of present-day Indonesia were determined at this time.